Caracterización y Análisis de la sustentabilidad de tunas (Opuntia Ficus-Indica) en el sector de Alpamalag. - Tacipanta Copara, Mayuri Edith (2023)
The present research work was carried out in the Alpamalag sector of the city of Pujilí, province of Cotopaxi, allowing us to obtain information for the evaluation of the sustainability of the tuna fruit, through indicators that allow us to detect aspects of complex systems that allow us to improve and guarantee the quality of life of the producers. The main objective was to characterize the production of prickly pear for sustainability in the Alpamalag sector of Pujilí with economic, environmental and sociocultural sustainability indicators through the application of a survey of 43 questions asked to the producers, according to Sarandón's methodology, data was implemented to evaluate the following indicators: Economic indicator IK with a value of 3.47 Environmental indicator IE the value obtained was 2.61 and the socio- cultural indicator ISC obtained a value of 2.63 this allowed obtaining a general sustainability index with a total value of 2.90. Finally, it is concluded that it is not sustainable and that urgent methods and techniques should be applied to improve the sustainability indicators for the benefit of the society of the Alpamalag sector, since they are still very affected by the standard of living they have up to now, which does not allow them to have a good quality of life.